Are regional differences in basketball already established in under-18 games? - Haruhiko Madarame (Universidade Estadual Paulista (UNESP), 2018)
Abstract Aims: To identify regional differences in basketball games for under-age categories, this study analyzed game-related statistics of four continental championships for under-18 (U18) men. Methods: A total of 149 games from each continental championship for U18 men held in 2016 were analyzed. A one-way analysis of variance followed by a Bonferroni post hoc test was performed to assess differences in game-related statistics between the continents (Europe, Africa, America, Asia). A discriminant analysis was performed to identify game-related statistics which discriminate among the continents. Results: The U18 African championship, which was characterized by a high number of free throws, was clearly discriminated from any other U18 continental championship. Among the other U18 continental championships excluding the African championship, the biggest difference was observed between the European and the Asian championships. The U18 European championship was characterized by a low number of possessions and a high number of assists, whereas the U18 Asian championship was characterized by a high number of possessions and a low number of assists. Both possessions and assists showed high numbers in the U18 American championship. Conclusion: This study identified regional differences in basketball games among four continental championships for U18 men held in 2016. It is suggested that basketball games for under-age categories are played in a different manner in each region of the world. The information derived from this study will help players and coaches of under-age national teams prepare for international competitions.